Clinical outcome of appendectomy: laparoscopic vs open technique - Rather, Jan M.; Manzoor, Sobia; Shah, Mubashir (International Surgery Journal, 2021)
Background: Acute appendicitis is a common abdominal surgical emergency. Appendectomy has been proven to be the standard care for the treatment of acute appendicitis. Objective of the study was to compare laparoscopic and open appendectomy in terms of clinical outcome and complication rates. Methods: This was a single centric, retrospective study conducted at SKIMS, Soura from May 2018 to April 2021. Open and laparoscopic appendectomy patients were compared in terms of operative times, conversion rate, complication rates and duration of hospital stay. Results: Total 120 patients were included in this study with 40 in laparoscopic group while 80 patients in the open group. Increased operative time in laparoscopic group (p=0.033) and longer duration of hospital stay (p=0.021) with open group while as comparable complication rate in both procedures were observed. Higher rates of intra-abdominal collection in laparoscopic group as compared to open group Conclusions: Both laparoscopic and open appendectomy procedures can be performed routinely for acute appendicitis without the additional risks of complications.